MetaBridge: An Integrative Multi‐Omics Tool for Metabolite‐Enzyme Mapping. Issue 1 (21st March 2020) - Blimkie, Travis; Lee, Amy Huei‐Yi; Hancock, Robert E.W.
Abstract: MetaBridge is a web‐based tool designed to facilitate the integration of metabolomics with other "omics" data types such as transcriptomics and proteomics. It uses data from the MetaCyc metabolic pathway database and the Kyoto Encyclopedia of Genes and Genomes (KEGG) to map metabolite compounds to directly interacting upstream or downstream enzymes in enzymatic reactions and metabolic pathways. The resulting list of enzymes can then be integrated with transcriptomics or proteomics data via protein‐protein interaction networks to perform integrative multi‐omics analyses. MetaBridge was developed to be intuitive and easy to use, requiring little to no prior computational experience. The protocols described here detail all steps involved in the use of MetaBridge, from preparing input data and performing metabolite mapping to utilizing the results to build a protein‐protein interaction network. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Mapping metabolite data using MetaCyc identifiers Basic Protocol 2 : Mapping metabolite data using KEGG identifiers Support Protocol 1 : Converting compound names to HMDB IDs Support Protocol 2 : Submitting mapped genes produced by MetaBridge for protein‐protein interaction (PPI) network construction